E. E. ZAMYSLOVSKY ABOUT RUSSIAS FOREIGN POLICY DURING THE SECOND HALF OF THE XVI TH CENTURY – THE XVII TH CENTURY - E. F. Zdanovich (Вестник Кемеровского государственного университета, 2015)
The article analyzes the views of Egor Zamyslovsky to the most important events of Russian history. In the center of attention of the researcher was the history ofRussiaof the XVII century. In the scientific searches, the historian addressed to Ivan IV and Fedor Alekseevich's reign. The merit of the scientist is, undoubtedly, that he made emphasis on the analysis of the history of foreign policy of the Russian state in XVI – XVII centuries. Zamyslovsky in details acquaints with the contents of little-known periods of the Russian history. The historian managed to collect and comment huge historiographic material, which is important for the development of historical science. Historiographer’s work gained recognition among his contemporaries. In spite of the fact that Zamyslovsky realized not all plans, the master thesis «Fedor Alekseevich's Reign» served as the base for further research ofRussiaof the XVII century.